A systematic comparison of the accuracy of monocular RGB tracking and LiDAR for neuronavigation. Issue 6 (17th October 2022) - Khan, Talha; Biehl, Jacob T.; Andrews, Edward G.; Babichenko, Dmitriy
Abstract: With the advent of augmented reality (AR), the use of AR‐guided systems in the field of medicine has gained traction. However, the wide‐scale adaptation of these systems requires highly accurate and reliable tracking. In this work, the tracking accuracy of two technology platforms, LiDAR and Vuforia, are developed and rigorously tested for a catheter placement neurological procedure. Several experiments (900) are performed for each technology across various combinations of catheter lengths and insertion trajectories. This analysis shows that the LiDAR platform outperformed Vuforia; which is the state‐of‐the‐art in monocular RGB tracking solutions. LiDAR had 75% less radial distance error and 26% less angle deviation error. Results provide key insights into the value and utility of LiDAR‐based tracking in AR guidance systems.